Design and in silico study of the novel coumarin derivatives against SARS-CoV-2 main enzymes - YALÇIN, BAHATTİN; ÖZDEMİR, MÜCAHİT (TAYLOR & FRANCIS INC, 2020)
The novel coronavirus (SARS-CoV-2) causes severe acute respiratory syndrome and can be fatal. In particular, antiviral drugs that are currently available to treat infection in the respiratory tract have been experienced, but there is a need for new antiviral drugs that are targeted and inhibit coronavirus. The antiviral properties of organic compounds found in nature, especially coumarins, are known and widely studied. Coumarins, which are also metabolites in many medicinal drugs, should be investigated as inhibitors against coronavirus due to their pharmacophore properties (low toxicity and high pharmacokinetic properties). The easy addition of substituents to the chemical structures of coumarins makes these structures unique for the drug design. This study focuses on factors that increase the molecular binding and antiviral properties of coumarins. Molecular docking studies have been carried out to five different proteins (Spike S1-subunit, NSP5, NSP12, NSP15, and NSP16) of the SARS-CoV-2 and two proteins (ACE2 and VKORC1) of human. The best binding scores for 17 coumarins were determined for NSP12 (NonStructural Protein-12). The highest score (-10.01 kcal/mol) in the coumarin group is 2-morpholinoethan-1-amine substituted coumarin. Molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) analyses of selected ligand-protein complexes were performed. The binding energies in each 5 ns were calculated and it was found that the interaction between ligand and target protein were stable. Communicated by Ramaswamy H. Sarma
Keywords: Coronavirus; SARS-CoV-2; MM-PBSA; coumarin; molecular docking; drug design